Radiation-induced osteosarcoma of the maxilla. - Kasthoori, J.J.; Wastie, M.L. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2006)
Radiation-induced sarcomas are well-known though uncommon potential late sequelae of radiation therapy. We report irradiation-induced osteosarcoma involving the maxilla following treatment of nasopharyngeal carcinoma in a 44-year-old man who presented with painful cheek swelling. Radiographs and computed tomography showed a large destructive lesion of the left maxilla. Diagnosis of osteosarcoma was confirmed by excision biopsy.